C-Glycosidic Genistein Conjugates and Their Antiproliferative Activity - Aleksandra Rusin; Maciej Chrubasik; Katarzyna Papaj; Grzegorz Grynkiewicz; Wiesław Szeja (Journal of Chemistry)
This paper presents our attempt to investigate scopes and the limitations of olefin cross-metathesis (CM) reaction in the synthesis of complex C-glycosides of genistein and evaluation of their antiproliferative activities. Novel genistein glycoconjugates were synthesized with the utility of CM reaction initiated by first and second generation of Grubbs catalysts. The relative reactivity of utilized olefins, based on categories proposed by Grubbs, was estimated. In vitro experiments in cancer cell lines showed that the selected derivatives (3a and 3f) exhibited higher antiproliferative potential than the parent compound, genistein, and were able to block the cell cycle in the G2/M phase. The observed mechanism of action of C-glycosidic derivatives was similar to the activity of their O-glycosidic counterparts. These compounds were stable in culture medium. The obtained results show that our approach to genistein modification with application of cross-metathesis reaction allowed to obtain stable glycoconjugates with improved anticancer potential, compared to the parent isoflavone.